INNOVATIVE MANAGEMENT STRATEGIES FOR EDUCATIONAL INSTITUTIONS: ADDRESSING CHALLENGES AND LEVERAGING OPPORTUNITIES IN THE DIGITAL AGE (ІННОВАЦІЙНІ ПРОЦЕСИ ОСВІТНЬОЇ СФЕРИ УКРАЇНИ ТА КРАЇН ЦЕНТРАЛЬНОЇ ЄВРОПИ: СТАН, ПРОБЛЕМИ І ПЕРСПЕКТИВИ, 2024)
.